(untitled) (Kronika Bydgoska, 2020)
This text presents expertise written by lawyer Jan Maciaszek, the first appointed Polish mayor of the city of Bydgoszcz in 1920. It was made at the request of the church authorities in relation to the efforts of Germ an Catholics for recognizing the existence of the Germ an Catholic com m unity (and thus a separate parish) in Bydgoszcz. The original is in the collection of the Archdiocesan Archive in Gniezno and has never been published. The expertise provided by Jan Maciaszek contains m any unknow n details and facts from the life of the Bydgoszcz parish and national relations in the city in the period between the 1890s and the 1920s.